Graphene oxide improves the biocompatibility of collagen membranes in an in vitro model of human primary gingival fibroblasts. (13th September 2017) - De Marco, Patrizia; Zara, Susi; De Colli, Marianna; Radunovic, Milena; Lazović, Vladimir; Ettorre, Valeria; Di Crescenzo, Antonello; Piattelli, Adriano; Cataldi, Amelia; Fontana, Antonella
Abstract: Commercial collagen membranes are used in oral surgical procedures as scaffolds for bone deposition in guided bone regeneration. Here, we have enriched them with graphene oxide (GO) via a simple non-covalent functionalization, exploiting the capacity of oxygenated carbon functional moieties of GO to interact through hydrogen bonding with collagen. In the present paper, the GO-coated membranes have been characterized in terms of stability, nano-roughness, biocompatibility and induction of inflammatory response in human primary gingival fibroblast cells. The obtained coated membranes are demonstrated not to leak GO in the bulk solution, and to change some features of the membrane, such as stiffness and adhesion between the membrane and the atomic force microscopy (AFM) tip. Moreover, the presence of GO increases the roughness and the total surface exposed to the cells, as demonstrated by AFM analyses. The obtained material is biocompatible, and does not induce inflammation in the tested cells.